The Implementation of Character Education Design through Integrated Curriculum at Islamic University - Usiono Usiono; Syarifah Widya Ulfa; Khairuddin Tambusai (STAI Hubbulwathan Duri, 2022)
This study aimed to determine the design of character education implementation through an integrated curriculum at a state Islamic university in Medan. This research conducted a qualitative case study method. The research informants are eight people, consisting of 4 main informants and 4 supporting informants. The data is collected through observation and focus group discussion. Data objectivity is achieved through the triangulation of data sources. The data is analysed using ATLAS.Ti 22 software version 8. The data is presented in the form of images, tables, and descriptions. The research results show that character development begins with the implementation of character education in the educational environment so that it becomes a habit that shapes character. The strength of the factors that helped or held someone back had an effect on how they grew and changed. It can be said that lecturers can be the most important role models on campus when it comes to character education.